The in silico identification of small molecules for protein-protein interaction inhibition in AKAP-Lbc–RhoA signaling complex. (April 2017) - Khan, Asifullah; Munir, Mehwish; Aiman, Sara; Wadood, Abdul; Khan, Arif-ullah
Graphical abstract: Highlights: The A-Kinase Anchoring Protein, i.e. AKAP-Lbc is involved in cardiac repolarization by mediating Rho GTPases activation. The oncogenic AKAP-Lbc causes the RhoA GTPase hyperactivity based hypertrophic cardiomyocytes. The in silico drug discovery strategies identified drug-like small molecules capable to inhibit the interactions between AKAP-Lbc and RhoA. Abstract: The rational design of small molecules that mimic key residues at the interface of interacting proteins can be a successful approach to target certain biological signaling cascades causing pathophysiological outcome. The A-Kinase Anchoring Protein, i.e. AKAP-Lbc, catalyses nucleotide exchange on RhoA and is involved in cardiac repolarization. The oncogenic AKAP-Lbc induces the RhoA GTPase hyperactivity and aberrantly amplifies the signaling pathway leading to hypertrophic cardiomyocytes. We took advantage of the AKAP-Lbc– RhoA complex crystal structure to design in silico small molecules predicted to inhibit the associated pathological signaling cascade. We adopted the strategies of pharmacophore building, virtual screening and molecular docking to identify the small molecules capable to target AKAP-Lbc and RhoA interactions. The pharmacophore model based virtual screening unveils two lead compounds from the TIMBAL database of small molecules modulating the targeted protein-protein interactions. The molecular docking analysis revealed the lead compounds' potentialities to establish the essential chemical interactions with the key interactive residues of the complex. These features provided a road map for designing additional potent chemical derivatives and fragments of the original lead compounds to perturb the AKAP-Lbc and RhoA interactions. Experimental validations may elucidate the therapeutic potential of these lead chemical scaffolds to deal with aberrant AKAP-Lbc signaling based cardiac hypertrophy.